Bildung Im Digitalen Wandel: Die Bedeutung Für Das Pädagogische Personal Und Für Die Aus- Und Fortbildung 2020
DOI: 10.31244/9783830991991.02
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisierung in der frühen Bildung: Der Umgang mit digitalen Medien im Spannungsfeld zwischen Schutzraum und Schlüsselkompetenz

Abstract: Bibliografi sche Informationen der Deutschen Nationalbibliothek Die Deutsche Nationalbibliothek verzeichnet diese Publikation in der Deutschen Nationalbibliografi e; detaillierte bibliografi sche Daten sind im Internet über http://dnb.dnb.de abrufb ar. Dieses Projekt wird aus Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01JD1800B gefördert. Die Verantwortung für den Inhalt dieser Veröff entlichung liegt bei den Autorinnen und Autoren.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…However, as the present study shows, this is not the case in all Western countries. Studies have demonstrated that ones' own pedagogical media competencies are decisive for whether media are a central component in everyday early childhood education with children (Nieding & Klaudy, 2020). The state of research regarding early childhood educators' media competence is a desideratum (Knauf, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the present study shows, this is not the case in all Western countries. Studies have demonstrated that ones' own pedagogical media competencies are decisive for whether media are a central component in everyday early childhood education with children (Nieding & Klaudy, 2020). The state of research regarding early childhood educators' media competence is a desideratum (Knauf, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the German-speaking world, the field of early childhood education has very few connections to virtual teaching/ learning platforms, and general knowledge of further training programmes is somewhat rare (Buschle & König, 2018). Nieding and Klaudy (2020) emphasised in their study that early childhood educators' attitude and approach towards digital media is a major factor in whether digital media are used. Early childhood educators are currently required to use digital media to meet instructional goals (keyword: educational plans) whilst simultaneously fulfilling pedagogical requirements in the context of current societal developments.…”
Section: (Online) Professional Development Programmes Could Be the Wa...mentioning
confidence: 99%
“…Design Thinking). Wie bereits im Review des letzten Bandes (siehe Nieding & Klaudy, 2020) beschrieben, sind Kompetenzen und Haltung der pädagogischen Fachkräfte zentrale Schlüsselelemente für einen sicheren Einsatz digitaler Medien in der Praxis. Dennoch schätzt weiterhin ein Großteil der befragten Fachkräfte die technischen Medienkenntnisse von Erziehenden als mangelhaft ein (72 %).…”
Section: Hürdenunclassified
“…Currently existing studies mostly focus on promoting the application of artificial intelligence technology in preschool education (Jiang, 2020). Others are stressing the potential impact on teaching and learning (Nieding et al, 2020;Tuomi, 2018).…”
Section: Introductionmentioning
confidence: 99%